2023
DOI: 10.1111/nep.14254
|View full text |Cite
|
Sign up to set email alerts
|

Urinary liver‐type fatty acid binding protein is a biomarker reflecting renal damage and the ameliorative effect of drugs at an early stage of histone‐induced acute kidney injury

Keiichi Ohata,
Takeshi Sugaya,
Hanh Nhung Nguyen
et al.

Abstract: AimCirculated histones play a crucial role in the pathogenesis of infectious diseases and severe trauma, and it is one of the potential molecular targets for therapeutics. Recently, we reported that histone is one of the causative agents for urinary L‐FABP increase. However, the mechanism is still unclear, especially in severe cases. We further investigated the mechanism of urinary L‐FABP increase using a more severe mouse model with histone‐induced kidney injury. This study also aims to evaluate the therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…At present, plasma L-FABP is used as a novel biomarker for injury in many organs, especially the kidneys and intestines, which are the main sources of L-FABP production. The study of L-FABP used as a biomarker of acute kidney injury (AKI) showed that urinary L-FABP elevation correlates with the severity of AKI, particularly in the early stages, and can be used for drug administration or tissue transplant monitoring [38,39]. Serum L-FABP and trefoil factor-3 levels decrease in the case of displaced abomasum (DA) in ruminants in contrast with increasing leptin levels.…”
Section: Discussionmentioning
confidence: 99%
“…At present, plasma L-FABP is used as a novel biomarker for injury in many organs, especially the kidneys and intestines, which are the main sources of L-FABP production. The study of L-FABP used as a biomarker of acute kidney injury (AKI) showed that urinary L-FABP elevation correlates with the severity of AKI, particularly in the early stages, and can be used for drug administration or tissue transplant monitoring [38,39]. Serum L-FABP and trefoil factor-3 levels decrease in the case of displaced abomasum (DA) in ruminants in contrast with increasing leptin levels.…”
Section: Discussionmentioning
confidence: 99%
“…
The recent work by Ohata et al, titled "Urinary liver-type fatty acid binding protein is a biomarker reflecting renal damage and the ameliorative effect of drugs at an early stage of histone-induced AKI," has piqued our interest. 1
…”
mentioning
confidence: 99%